Identifying the quality markers and optimizing the processing of Gastrodiae rhizoma to treat brain diseases - Fu, Yan; Xu, Qingqing; Zhang, Jinqiang; Kang, Chuanzhi; Yang, Changgui; Guo, Lumei; Zhang, Chenggang; Zhou, Tao; Xiao, Chenghong (Frontiers in Pharmacology, 2024)
Background: Gastrodiae rhizoma (GR), the dried tuber of Gastrodia elata Bl., has been used for centuries to treat brain diseases, such as Alzheimer's disease, major depressive disorder and cerebral ischemia. However, the processing of GR is complex and varied, resulting in unstable clinical treatment effects. The processing protocol can significantly affect the active ingredients and curative effects of GR. We can optimize the processing of GR by identifying quality markers to treat brain diseases. Methods: Fresh tuber of Gastrodia elata Bl. were processed in eight different protocols, and their resulting content in potentially bioactive compounds was compared using liquid chromatography-mass spectrometry and the potential quality markers of GR were screened by stoichiometric analysis. Potential quality markers of GR targeted Alzheimer's disease, major depressive disorder and cerebral ischemia were identified using network pharmacology. And the potentially neuroprotective effects of these components were validated through simulated docking to likely protein targets. Finally, the fit degree analysis was carried out by using different composition ratio and the proportion of disease component degree value, and the therapeutic effects of different processing methods on Alzheimer's disease, major depressive disorder and cerebral ischemia were clearly targeted.Results: We identified 32 potential therapeutic components and screened 13 quality markers in GR, five of these quality markers (Galactinol, Glucosyringic acid, Parishins C and E, and S-(4-hydroxybenzyl)-glutathione) show efficacy against all three brain diseasesbrain diseases, and steaming and microwave-drying during processing can optimize the component of these quality markers to treat these three brain diseases. Conclusion: The processing protocol can significantly affect the therapeutic components of GR, and may affect the effectiveness of GR in treating brain diseases. According to different therapeutic purposes of GR to adopt the corresponding optimal processing methods may improve its efficacy against brain diseases.